TINJAUAN LAMA WAKTU PELAYANAN REKAM MEDIS POLIKLINIK PENYAKIT DALAM RUMAH SAKIT SALAK KOTA BOGOR TAHUN 2021 - Agung Martin; Dina Sonia (Journal of Innovation Research and Knowledge, 2021)
The hospital has a mission to provide quality and affordable health services to the community in order to improve the health status of the community, one of which is through fast patient waiting times. This study aims to analyze the length of waiting time (arrival process, service, human resources) for outpatient services at the Internal Medicine Polyclinic at Salak Hospital, Bogor. During the service process, there are several obstacles that occur, including the patient does not bring a complete file/guarantee, inadequate room, and limited human resources who are experts in refraction and medical records. The waiting time at the Salak Hospital in Bogor is still quite long(> 60 minutes) due to the large number of patients, interference with the insurance network which makes the waiting time longer, the distribution of medical record files is often late. It can be concluded that a person or group of people has the opportunity to make people aware of their own abilities, while at the same time implementing the actions of certain people or groups. In addition, it can be interpreted as the ability to control, dominate, or manipulate the actions of others (Rollo May 1972), thus it can be concluded that a patient can affect the length of waiting time in Health Service Agencies.